Efisiensi Pengelolaan Dana Ziswaf Pada Lembaga Sosial Pesantren Tebuireng (LSPT) Jombang dengan Menggunakan Data Envelopment Analysis - Moch. Zainuddin (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
Islamic economics exists to realize the benefit of humans both in the world and in the hereafter. This is stated in the Maqasid al-Syariah as a guide for humans to navigate life. Ziswaf comes with various benefits including protecting human assets and also fulfilling the condition of the economic need around so that they are able to fulfill basic needs in life. In coordinating ziswaf, ziswaf institutions are needed to utilize them effectively and efficiently, both in terms of collection and distribution. Efficiency measurement is one of the performance indicators of an institution to find out how far the fund management is carried out by the institution, and whether it is optimal and according to the target to be achieved. Performance measurement can provide direction and strengthen the goals of a ziswaf institution going forward. Data Envelopment Analysis (DEA) aims to measure an institution with many inputs and outputs. The use of DEA method is done by comparing the processed results through input and output variables. This study uses Data Envelopment Analysis (DEA) in its measurement. The approach in this research is the intermediation approach. While the assumption is using (Variable VRS) which is oriented towards input and output. The results show that the Tebuireng Islamic Boarding School (LSPT) Jombang in 2015 experienced 100% efficient performance, in 2016 experienced 100% efficient performance, in 2017 experienced inefficiency performance of %, in 2018 experienced inefficiency performance of %, in 2019 experienced 100% efficient performance.